Nutritional intake during a 244 km multisport ultraendurance race - Colombani, P. C.; Mannhart, C.; Wenk, C.; Frey, W. O. (Pakistan Journal of Nutrition, 2002)
Data about the nutrition during ultraendurance competitions are scarce, with the exceptions of few case reports. Because very long lasting sports events become more and more popular, we aimed to describe the nutritional intake during an extreme ultraendurance race carried out in Switzerland in 1998. The ultraendurance multisport race was 244 km long (48 km mountain biking, 122 km road cycling, 28 km roller blading, 3.5 km swimming, 42.5 km running; total altitude difference ±4000 m). The 12 male finishers participating in the study completed the race in a median (and range) time of 18.6 (17.0-19.8) hours. Their energy intake during the race was 22.6 (12.4-33.6) MJ and corresponded to 44 % of their estimated energy expenditure. Carbohydrate, protein, net fluid, and net sodium intake amounted to 60 (36-90) g·h , 0.8 (0.1-2.4) g·kg body -1 -1 mass, 560 (310-790) mL·h , and 13 (7-19) mmol·L net fluid intake, respectively. In conclusion, the nutrition during the -1 -1 ultraendurance race was similar to the one recommended for shorter events like a marathon run and the focus was set upon a high carbohydrate intake.